Changes in psychological and biochemical indices of stress across a competitive season in age-group swimmers - Kerr, G.; VanHeest, J. L.; Rodgers, C. D. (Medicine & Science in Sports & Exercise, 1998)
Over a five month period there was no difference in the sources of perceived stress, but significant increase in the number of stress symptoms and cortisol levels and a decrease in salivary IgA levels.